Fabrication of novel oxochalcogens halides of manganese and tin nanocomposites as highly efficient photocatalysts for dye degradation and excellent antimicrobial activity - Umar, Misbah; Mansoor, Sana; Javed, Mohsin; Hussain, Nadia; Bajaber, Majed A.; Iqbal, Shahid; Alhujaily, Ahmad; Mohyuddin, Ayesha; Ajaz, Humayun; Rauf, Abdul; Bahadur, Ali; Al-Fawzan, Foziah F.; et al. (Frontiers in Materials, 2023)
The dark brown and white crystals of manganese and tin (Mn2Se3Cl2O7 & SnSe3O4Cl) have been synthesized by solid-state reaction at 450 °C. The morphology and the elemental analysis of newly synthesized compounds were studied by SEM and EDX Analysis. SEM analysis reveals that the particle size for Mn2Se3Cl2O7 was found to be 0.2-2.5 micrometers and for SnSe3O4Cl 2.0-6.0 micrometers. The EDX studies showed the presence of Mn, Se, O, Cl, and Sn elements. Powdered XRD confirmed the presence of a new phase present in these compounds. Under UV-vis irradiation, the kinetics of methylene blue (MB) degradation catalyzed by produced nanoparticles were monitored. The dye degradation efficiency was estimated, and results reveals that after 150min of irradiation, almost 75% of the dye was degraded in the presence of Mn compound while 71% degradation was shown by Sn compound. Both composites display antimicrobial activity against Staphylococcus aureus and Escherichia coli with a maximum value of 34.5mm. The maximum antimicrobial activity shown by Mn-incorporated nanocomposites estimated at 32.5 mm was against gram-positive bacteria and 26.4 mm against gram-negative bacteria. Similarly, the maximum antifungal activity shown by Sn incorporated estimated at 33.9 mm was compared to gram-positive bacteria and 27.8 mm against gram-negative bacteria.